Anthropometric Linear Measurements of Female Athletes in the Italian National Athletic Teams - Matarazzo, A.; D'anastasio, R. (International Journal of Morphology, 2022)
Anthropometry is essential to understand the predisposition of an athlete to practice a specific sporting activity, to assess their fitness, and in association with functional parameters, to identify any correlations between their anthropometric profile and their sport performance. Here, we present the anthropometric profiles of athletes of the Italian national teams, who represented Italy in the 2019-2020 competitive season in the following sports: artistic (n=4) and rhythmic (n=12) gymnastics; distance swimming (speciality: 100 m freestyle) (n=14); synchronized swimming (n=10); and basketball (n=6). We also consider a group of sedentary women (n=22) for comparisons. The following anthropometric measurements were taken for each woman: stature; anterior trunk height (i.e., suprasternal- symphysion distance); chest circumference passing through the mesosternal point; biacromial diameter (i.e., akromion-akromion distance); wrist circumference; abdominal circumference passing through the omphalion and the lumbale; hip circumference; height of lower limb (i.e., epitrochanter-planta distance). Height was a selective factor in both basketball, which requires tall athletes, and artistic gymnastics, where in contrast, well-muscled athletes of small stature are required. In aquatic sports, the constitutional habitus is characterized by good development of the upper body compared to the lower limbs. The selection of elite athletes takes place primarily through anthropometric analyses, although other functional and psychological factors also influence their sports performance.